The complete chloroplast genome sequence of Pittosporum kerrii: the first Pittosporaceae plastome - Yi Wang; Chuan Zhao; Yunqing Li (Mitochondrial DNA. Part B. Resources, 2019)
The first complete chloroplast genome (cpDNA) sequence of Pittosporum kerrii was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 153,581 bp in length, contains a large single-copy region (LSC) of 84,940 bp and a small single-copy region (SSC) of 18,741 bp, which were separated by a pair of inverted repeats (IR) regions of 24,950 bp. The genome contains 132 genes, including 87 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. The overall GC content of the whole genome is 38.3%, and the corresponding values of the LSC, SSC, and IR regions are 36.5, 32.5, and 43.3%, respectively. Further, phylogenomic analysis showed that P. kerrii clustered in a unique clade in order Apiales.